The reasons of the nursing staff to notify adverse events - Paiva, Miriam Cristina Marques Da Silva De; Popim, Regina Célia [UNESP]; Melleiro, Marta Maria; Tronchim, Daisy Maria Rizatto; Lima, Silvana Andréa Molina [UNESP]; Juliani, Carmen Maria Casquel Monti [UNESP] (Escola de Enfermagem de Ribeirão Preto / Universidade de São Paulo, 2014)
OBJECTIVE:this research aimed to understand the motivation for reporting adverse events from the perspective of nursing staff in the work environment.METHOD:qualitative study that used the phenomenology of Alfred Schutz for reference, which offers a systematic approach to understand the social aspects of human action. Data were collected by open interviews with 17 nurses and 14 technicians/assistant nurses in a university hospital.RESULTS:motivation was revealed through six categories: all types of occurrences must be reported; the incident report is an auxiliary instrument to health care provision management; the culture of punishment in transition; nurses as the agents responsible for voluntary reporting; sharing problems with higher management and achieving quality in the work process.DISCUSSION:it was unveiled that, when reporting adverse events, team members perceived themselves to be in a collaborative relationship with the institution and trusted that they would receive administrative support and professional security, which encouraged them to continue reporting. Reporting allows health care professionals to share responsibilities with managers and encourages corrective actions.FINAL CONSIDERATIONS:the study revealed the nursing staff's motivation for adverse event reporting, contributing to reflections on institutional policies aimed at patient safety in health care.

OBJETIVO: compreender a motivação da equipe de enfermagem para a notificação de eventos adversos no ambiente de trabalho. MÉTODO: estudo qualitativo, utilizando os referenciais da fenomenologia de Alfred Schutz, que oferece abordagem sistemática para compreensão dos aspectos sociais da ação humana. Os dados foram coletados por meio de entrevistas abertas com 17 enfermeiros e 14 técnicos/auxiliares de enfermagem de um hospital universitário. RESULTADOS: a motivação foi revelada através de seis categorias: todo tipo de ocorrência deve ser notificado; a notificação como sistema de auxílio à gestão da assistência; a cultura da punição em transição; o enfermeiro como responsável pela notificação voluntária; compartilhar problemas com a administração superior e alcançar qualidade no processo de trabalho. DISCUSSÃO: ao notificar o evento adverso, os profissionais percebem-se em relação de colaboração com a instituição e confiam que lhes serão conferidos suporte administrativo e segurança profissional, condições que os encorajam a continuar notificando. Notificar permite à equipe de enfermagem compartilhar responsabilidades com a administração superior e, ainda, estimula ações corretivas. CONSIDERAÇÕES FINAIS: o estudo revela a motivação da equipe de enfermagem para a notificação de eventos adversos, contribuindo para a reflexão das políticas institucionais voltadas para a segurança do paciente nos serviços de saúde.

OBJETIVO: comprender la motivación del equipo de enfermería para la notificación de eventos adversos en el ambiente de trabajo. MÉTODO: estudio cualitativo que utilizó los referenciales de la fenomenología de Alfred Schutz, que ofrece aproximación sistemática para comprender los aspectos sociales de la acción humana. Los datos fueron recolectados mediante entrevistas abiertas con 17 enfermeros y 14 técnicos/auxiliares de enfermería de un hospital universitario. RESULTADOS: la motivación fue revelada a través de seis categorías: todo tipo de ocurrencia debe ser notificado; la notificación como sistema de auxilio a la gestión de la atención; la cultura de punición en transición; el enfermero como responsable por la notificación voluntaria; compartir problemas con la administración superior y alcanzar calidad en el proceso de trabajo. DISCUSIÓN: al notificar el evento adverso, los profesionales se perciben en una relación colaborativa con la institución y confían que les serán conferidos soporte administrativo y seguridad profesional, condiciones que les estimulan a continuar notificando. Notificar permite al equipo de enfermería compartir responsabilidades con la administración superior y estimula acciones correctivas. CONSIDERACIONES FINALES: el estudio revela la motivación del equipo de enfermería para la notificación de eventos adversos, contribuyendo hacia la reflexión de las políticas de enfermería dirigidas a la seguridad del paciente en los servicios de salud.
Motivos del equipo de enfermería para la notificación de eventos adversos
Motivos da equipe de enfermagem para a notificação de eventos adversos
Keywords: Segurança; Controle de Riscos; Erros Médicos; Enfermagem; Pesquisa Qualitativa; Safety; Risk Management; Medical Errors; Nursing; Qualitative Research